Impact of STAT/SOCS mRNA Expression Levels after Major Injury. (6th February 2014) - Brumann, M.; Matz, M.; Kusmenkov, T.; Stegmaier, J.; Biberthaler, P.; Kanz, K.-G.; Mutschler, W.; Bogner, V.
Abstract : Background . Fulminant changes in cytokine receptor signalling might provoke severe pathological alterations after multiple trauma. The aim of this study was to evaluate the posttraumatic imbalance of the innate immune system with a special focus on the STAT/SOCS family. Methods . 20 polytraumatized patients were included. Blood samples were drawn 0 h–72 h after trauma; mRNA expression profiles of IL-10, STAT 3, SOCS 1, and SOCS 3 were quantified by qPCR. Results . IL-10 mRNA expression increased significantly in the early posttraumatic period. STAT 3 mRNA expressions showed a significant maximum at 6 h after trauma. SOCS 1 levels significantly decreased 6 h–72 h after trauma. SOCS 3 levels were significantly higher in nonsurvivors 6 h after trauma. Conclusion . We present a serial, sequential investigation in human neutrophil granulocytes of major trauma patients evaluating mRNA expression profiles of IL-10, STAT 3, SOCS 1, and SOCS 3. Posttraumatically, immune disorder was accompanied by a significant increase of IL-10 and STAT 3 mRNA expression, whereas SOCS 1 mRNA levels decreased after injury. We could demonstrate that death after trauma was associated with higher SOCS 3 mRNA levels already at 6 h after trauma. To support our results, further investigations have to evaluate protein levels of STAT/SOCS family in terms of posttraumatic immune imbalance.